Study in vitro of the Microleakage in the Pits and Fissures Sealed with Resin Sealant and Compomer - Dennis de Carvalho FERREIRA; Bartira Cruxên Gonçalves VOLSCHAN; Elisangela Lins Cavalcanti PIMENTEL; Katia Regina Hostilio Cervante DIAS (Association of Support to Oral Health Research (APESB), 2006)
Objective: The purpose of this study in vitro was to compair the microleakage in pits and fissures sealed with polyacid modified resin (Dyract™) and resin sealant (Fluoroshield™). Method: In this study, 36 sound permanent premolars were equally distributed into three groups: GI (Flu.), GII (Dyr.) e GC (Control-without sealant). The materials were applied and a DES/RE cycle was processed to simulate a high cariogenic challenge. For immersion in the Silver Nitrate solution (50%), the roots and anatomic crowns (2mm over the margin of the material) were protected with nail enamel. After that, the nail enamel was removed and the teeth included in epoxi resin. Each crown was longitudinally seccioned in vestibular-lingual direction, to evaluate the degree of microleakage in the enamel/sealant interface. The marginal microleakege was classified by three examinators and the scores were: 0-no die penetration, 1-half die penetration, 2-complete die penetration. Results: The results were statistically analised by ANOVA, Kruskal-Wallis and Mann-Whitney (p<0.05), the medium posts were: GI (35.97), GII (37.53), GC (90.00). There were no statistically significant differences between the materials and the control group showed the worst result. Conclusion: We concluded that Dyract™ had no evidence of microleakage. However we can't discarded the need of longitudinal clinical studies to verify resin's proprierties as the resistence and bond strenght and anticariogenics proprieties of glass ionomer cements.